#TITLE_ALTERNATIVE# - EFENDY (NIM 30504001), HADY
Technological advancement demands large consumption of refractory materials in the steelmaking industries. Monolithic refractory materials have future market prospect due to their simplicity in production process than that of conventional firebrick. Unfortunately, monolithic refractory materials have inferior mechanical properties compared to firebrick, although they were developed from similar raw materials. Thus, advanced researches on improving material properties are imperatively needed. Immediate challenge is to obtain a new process method and correct composition for fabricating better properties of monolithic refractory materials. MgO-C refractories are commonly used in steelmaking industry, as a cover-wall in Basic Oxygen Furnace (BOF), Electric Arc Furnace (EAF), and Converter, due to their corrosion resistance to both slag and thermal stresses. Direct contact of liquid metal with MgO-C reduces the carbon content, because of carbon oxidation producing CO2 gases. On the other hand, solid MgO forms on the surface which prevents further carbon reduction, as well as penetration of slag and metal liquid into refractory. However, there is a competition between MgO formation and carbon oxidation which enhances pores formation, and then reduces significantly the mechanical strength of materials. In this research monolithic refractory samples were prepared using 86% weight of MgO, graphite, and 3-7% weight of various antioxidant metals (Al, Mg, Si, Al-Mg, Al-Si). Coal tar oil, phenolic resin, and their combination were used as binders. The samples were heat treated up to 1400 degrees C in the ambient environment prior to the characterization of sample density, porosity Cold Crushing Strength (CCS), Modulus of Rupture (MOR) and Hot Modulus of Rupture (HMOR), according to ASTM standard measurement. Structural properties were examined using X-Ray Diffractometer (XRD), Fourier Transform Infrared (FT-IR), Scanning Electron Microscope/Energy Dispersive X-Ray Spectrometer (SEM/EDS), Differentian Thermal Analysis (DTA) and Thermogravimetri Analysis (TGA). It was found that better mechanical properties of monolithic refractory material can be produced using the combination of tar-resin binder. In this case, the use of formaldehyde resin has been reduced to the health environmentally acceptable level. The comparison was made among samples produced, using tar, resin, and tar-resin binders after heat treated at the operation temperature of 1200 degrees C. It is important to note that graphitization and pyrolysis process have taken place at temperature as low as 457.79oC and in liquid phase, respectively. This condition mediated graphite distribution in the monolithic refractory matrix, which in turn prevented corrosion and enhanced the oxidation resistances. Further phenomena were discussed in detail. Further improvement of mechanical properties was obtained by addition of metal antioxidant. Adding 5% Al suppressed the porosity to 49.91%, 5% Al-Mg increased the HMOR to 67.09%, 5% Al-Si enhanced MOR to 71.71%, and 7% Al-Mg reduced CCS to 10.25%. Without metal-antioxidant the decomposition of binder to form H2, H2O, CO and CO2 gases took place at 200oC. These gaseous products released through and opened up the pores which caused the carbon oxidation. The formed pores were about 15-20% at temperature higher than 800 degrees C. The spreading metal-antioxidant within the matrix acted as an immediate oxidation media to form metal-oxides, such as MgO, Al2O3, spinel (MgAl2O4), and forsterite (Mg2SiO4) through out the matrix. In addition, aluminum-carbide (Al4C3) was also formed, so that all of them prevented further pores formation and carbon oxidation, and therefore enhanced corrosion strength of monolithic refractory.